An Analysis Of Lesson Plan Designed By Junior High School English Teachers In Boyolali - Nugraheni, Febrianna Pramudya Setya, Aryati Prasetyarini, S.Pd, M.Pd, Dr.Dwi Haryanti, M.Hum (2014)
This research paper is conducted to describe the lesson plan designed by junior high school English teachers in Boyolali, especially in formulating indicators, teaching procedure, source and media, and evaluation based on PERMENDIKNAS 41 (Regulation of National Education Minister number 41).This research paper belongs to a descriptive evaluative research. The data are collected by seeking, collecting and giving code. The data are taken from SMP N 1 Boyolali, SMP N 4 Boyolali and SMP N 3 Mojosongo. They are divided into four, namely indicator, teaching procedure, source and media, and evaluation. The technique for analyzing the data is descriptive which comprises three procedures namely: selection of the instrument, aggregation and analysis of the data and interpretation the result. Based on the PERMEN 41, the percentage of indicators in lesson plan made by junior high school English teachers in Boyolali is 67,17 %. The percentage is categorized as good based on the theory of Suharsimi. The total percentage of teaching procedure in lesson plan made by Junior High School English teachers in Boyolali is 61,84 %. The percentage is categorized as good based on the theory of Suharsimi. The total percentage of source and media in lesson plan made by Junior High School English teachers in Boyolali is 29,76 %. The percentage is categorized as bad based on the theory of Suharsimi. The total percentage of evaluation in lesson plan made by Junior High School English teachers in Boyolali is 73,16 %. The percentage is categorized as good based on the theory of Suharsimi.